2008
DOI: 10.1038/oby.2008.227
|View full text |Cite
|
Sign up to set email alerts
|

Ability to Taste 6‐n‐Propylthiouracil and BMI in Low‐income Preschool‐aged Children

Abstract: Background: Sensitivity to the bitter compound 6-n-propylthiouracil (PROP) is genetically mediated. Sensitivity to PROP has been associated with weight status in both adults and children. Objective: To determine whether there is an association between PROP sensitivity and BMI in low-income children of diverse race/ethnicity, among whom there is a high prevalence of obesity. Methods and Procedures: Eighty-one preschool-aged children attending Head Start tasted a solution of 560 μmol/l PROP and reported whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 35 publications
5
58
3
Order By: Relevance
“…Both the studies assessed consumption of vegetables using food-frequency questionnaires in preschool children in the United States, but no significant association was found (Keller et al, 2002;Lumeng et al, 2008). These results were similar to those of our study.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Both the studies assessed consumption of vegetables using food-frequency questionnaires in preschool children in the United States, but no significant association was found (Keller et al, 2002;Lumeng et al, 2008). These results were similar to those of our study.…”
Section: Discussionsupporting
confidence: 82%
“…Some studies have found that PROP tasters do not like vegetables, such as raw spinach (Turnbull and Matisoo-Smith, 2002) and broccoli (Keller et al, 2002;Bell and Tepper, 2006), and soy foods (Gayathri Devi et al, 1997). Two previous studies assessed the relationship of usual consumption of vegetables and fruits with PROP sensitivity in children, but neither study found significant associations between them (Keller et al, 2002;Lumeng et al, 2008). There has been no report on the relationship between PROP sensitivity and soy food intake in children.…”
Section: Introductionmentioning
confidence: 96%
“…On the other hand, Garcia-Burgos and Zamora [13] evaluated the relationship between the facial reaction to the food bitterness and body mass index (BMI) and reported evidence of high levels of facial expression for bitterness in patients with a high BMI (p = 0.07). Lumeng et al [17] detected a 6-point higher BMI percentile among taster subjects than among those unable to perceive bitterness (non-tasters) in a sample of lowincome volunteers (p = 0.0002). Several studies also suggest that children incapable of sensing PROP [15] No correlations between bitterness perception and anthropometric variables, energy consumption or hormone levels Nasser et al…”
Section: Resultsmentioning
confidence: 99%
“…2008 [17] Six-point higher BMI percentile among taster subjects than among those unable to perceive bitterness (non-tasters) in a sample of low income volunteers…”
Section: Resultsmentioning
confidence: 99%
“…51-54 However, a direct relationship between TAS2R38 genotype, food intake, and body weight has not been detected in epidemiological studies 55,56 or in genome-wide studies of association with body mass index, a measure of obesity. 10,57,58 Thus, if alleles of this bitter receptor gene can directly affect food intake or body weight, they are too weak to be detected in the population as a group.…”
Section: Bitter: Poisoned With Pleasurementioning
confidence: 99%